Inverted-U aggregate investment curves in a dynamic game of advertising - Luca Lambertini; Georges Zaccour (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
We revisit the relationship between market power and firms' investment incentives in a noncooperative differential oligopoly game in which firms sell differentiated goods and invest in advertising to increase the brand equity of their respective goods. The feedback equilibrium obtains under open-loop rules, and aggregate expenditure on goodwill takes an inverted-U shape under both Cournot and Bertrand behaviour, provided product differentiation is sufficiently high. Total industry expenditure is higher under Cournot competition.
Keywords: C73; L13; M37; 330